Barrier from the Side of Stunting Management Policy in Rural Areas of Indonesia: A Qualitative Study - Tage, Petrus Kanisius Siga; Febriyanti, Erna (JURNAL INFO KESEHATAN, 2024)
This study examines the factors hindering effective stunting management in rural Indonesia, with a particular focus on government policy. Despite ongoing efforts, inadequate attention has been given to key policy-related challenges, including cross-sectoral coordination, merit-based recruitment, budget allocation, and community-based education. This study aims to identify policy barriers that hinder the implementation of stunting mitigation efforts in rural Indonesia. The method used A qualitative approach with a phenomenological design was employed. Data were collected through semi-structured interviews with 32 purposively selected participants, including regional and sub-district heads, village chiefs, health department leaders, and community health center directors, from January to August 2023. The results show that the analysis identified five primary barriers to stunting management: (1) Regulatory inconsistencies, including overlapping inter-agency guidelines that create ambiguity in implementation; (2) Human resource limitations, characterized by a shortage of skilled personnel and nepotistic recruitment practices; (3) Structural and institutional barriers, such as bureaucratic inefficiencies and inter-agency conflicts of interest; (4) Misallocated funding, driven by corruption and weak oversight, leading to ineffective budget distribution; and (5) Community-related factors, including poverty, low nutritional awareness, and unsupportive cultural practices. The conclusion is The conclusion is to addressing these barriers is essential for improving stunting management in rural Indonesia. Enhancing policy consistency, strengthening institutional frameworks, and improving resource allocation are key to overcoming existing challenges. The study recommends periodic regulatory evaluations, enhanced cross-sectoral coordination, and alignment of national policies with local needs. Establishing community-based recruitment and training systems through strategic partnerships could mitigate human resource constraints. Strengthening anti-corruption measures through independent oversight and digital reporting systems. Finally, fostering sustained community education through sociocultural approaches and local leader involvement is critical to increasing awareness and participation in stunting prevention efforts.